COMMUNITY SERVICES ON TODDLER DEVELOPMENT, INSIGHT FROM MATERNAL AND CHILD HEALTH (KIA) BOOK IN SURAKARTA - Siti Nurhidayati; Revi Gama Hatta Novika, Atriany Nilam Sari, Luluk Fajria Maulida, Rufidah Maulina, Nurul Jannatul Wa (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Disrupted child development will contribute to morbidity throughout the human life cycle. Based on the SUSENAS results, the Early Childhood Development Index (ECDI) of Indonesian children is still relatively good and has a value of 88.30%. However, the active role of families in supporting children's growth and development is still needed. The Maternal and Child Health (MCH) book is a pre-screening instrument thatcan be used by parents for stimulation and screening tools for growth problems and child developmental delays can be detected early from the closest family. The purpose of this community service is to optimize thegrowth and development of toddlers through the use of Maternal and Child Health (MCH) books at Posyandu Tangkas, Pasar Kliwon, Surakarta through a family empowerment approach. used a mixed-methods approach, combinig both quantitative and qualitative data from 24 respondents. we door to door doing growth and development screening and stimulation education assistance to mothers who have children under five. Each mother is interviewed regarding age, growth and development screening, education on how to stimulate child development with the KIA book, conduct early detection of growth and development using the Developmental Pre-Screening Questionnaire (KPSP) according to the child's age, and then provide assistance for 4 weeks to toddlers with questionable KPSP results through cooperation with posyandu management cadres.